DECLARATIONS OF WILL IN THE DIGITAL ENVIRONMENT AND WRAP CONTRACTS - Klasiček, Dubravka (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Declarations of will made in a digital environment are undeniably different from the ones done in a „physical” world and some persons might not be aware of their significance. Many people join various Internet Service Provider’s (ISP) sites daily. To do that, they usually have to, agree to terms of service (ToS) that govern said site. These declarations of will are sometimes direct: by clicking ’I agree’, a person knows that he/she has agreed to ToS, whether he/she has read them or not. What is more important, a person is aware (or should be) that he/she has entered into some sort of an agreement with an ISP – a clickwrap agreement. However, on some Web pages, a person is consenting to ISP’s ToS simply by staying on and browsing the page – browsewrap agreements. These declarations are not direct and a person is often unaware that he/she has entered into an agreement with ISP. Furthermore, ToS often change and an ISP will sometimes not inform users about it. In those instances, users will not be aware of the changes to ToS and that simply by continuing to use ISP’s services, they are agreeing to them. These are some of examples of will being declared in a digital environment, without the person declaring it being aware of what he/she has done. It seems that, for some reason, people take what happens online less seriously than what happens in a “physical” world. This paper will try to show that this is a serious mistake in a digital environment. Key words: declaration of will, terms of service (ToS), Internet Service Provider (ISP), online agreements, clickwrap / browsewrap agreements